Prepozicinis vardažodžių valdomas kilmininkas baltų, Pabaltijo suomių ir skandinavų kalbose (istorinė apžvalga) - Mathiassen, Terje (Baltistica, 1994)
THE PREPOSITIVE ADNOMINAL GENITIVE IN BALTIC, BALTO-FINNIC AND SCANDINAVIAN LANGUAGES: A HISTORICAL SURVEYThe article deals with the parallel preposited adnominal non-partitive genitive in Baltic, Balto-Finnic and Scandinavian languages from the point of view of diachrony, areal linguistics and language typology where the latter perspective is based mostly on Greenberg's language universals. Data from Scandinavian historical syntax (Braunmüller's studies in word order) reveal a far more complex picture concerning the historical roots of the preposited genitive in the Nordic languages than one can observe from the smooth surface of to-day's Swedish, Danish and Norwegian which corresponds so neatly with the Baltic and Balto-Finnic languages with respect to the phenomenon in question.
Keywords: istorinė kalbotyra; vardažodis; kilmininkas